(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Kitibha described in Ayurveda clinically stimulates with Psoriasis. According to modern medicine Psoriasis is an autoimmune disease. The treatment of Psoriasis is challenging due to its high reoccurrence rate and non-responsive to modern treatment also. But Ayurveda considers it has Kshudrakustha and is a curable disease. According to World Psoriasis Day consortium 125 million people worldwide approximately 2 to 3 percent of the total populations have psoriasis. Many studies show that between 10 to 30 percent of people with psoriasis also develop psoriatic arthritis. The present case report of 41 year old female suffering from Psoriasis since 15 years attended in OPD in CARICD, Delhi. On examination she has bright pink lesions with pronounced edges, covered with silvery white scales which were easily separated from the lesion. Under the scales there appears a pinkish moist tender skin. On scraping of the moist skin there appeared tiny blood droplets (Auspitz’s sign) in her left foot since 15 years. The patient was given Ayurvedic compounds orally along with Leech therapy for 84 days. After 84 days of medication and 12 shifts of leech application, the PASI score reduced from 21 to 6 and DLQI Scores reduced from 3 to 1.7 and marked improvement in sign and symptoms was noted. Since it is a case report, researcher can initiate a pilot study based on this report. The Ayurvedic compound along with leech application is found to be effective in the treatment of Kitibha (Psoriasis) in this study.